A Cross-sectional Study On The Impact Of The Covid-19 Pandemic On Psychological Outcomes: Multiple Indicators And Multiple Causes Modeling - Musheer A. Aljaberi; Naser A. Alareqe; Abdulsamad Alsalahi; Mousa A. Qasem; Sarah Noman; Md. Uzir Hossain Uzir; Lubna Ali Mohammed; Zine.El. Abiddine Fares; Chung-Ying Lin; Atiyeh M. Abdallah; Rukman Awang Hamat; Mohd Dzulkhairi Mohd Rani (Public Library of Science, 2024)
Indexed by SCOPUS/ERA